2019
DOI: 10.1177/1073191119869826
|View full text |Cite
|
Sign up to set email alerts
|

When Hindsight Is Not 20/20: Ecological Momentary Assessment of PTSD Symptoms Versus Retrospective Report

Abstract: Assessment of posttraumatic stress disorder (PTSD) has relied almost exclusively on retrospective memory of symptoms, sometimes over long intervals. This approach creates potential for recall bias and obscures the extent to which symptoms fluctuate. The aim of the present study was to examine the discrepancy between retrospective self-reporting of PTSD symptoms and ecological momentary assessment (EMA), which captures symptoms closer to when they occur. The study also sought to estimate the degree to which PTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 35 publications
7
42
2
Order By: Relevance
“…It may be easier to identify whether more concrete occurrences happened within a specific timeframe (e.g., Within the last 3 h, I interacted with a family member) compared to more subtle experiences which may be better measured over the course of a whole day (e.g., How melancholic did you feel today?). Interestingly, a study by Schuler et al (2019) found no significant differences between the retrospective reports of symptoms when compared to EMA-based reports of traumatic experiences. These findings may reflect the unique circumstances involved in recall of such experiences, which are inherently more emotionally extreme and may therefore be easier to recall, even retrospectively.…”
Section: Methodological Variation In Ema Researchmentioning
confidence: 92%
“…It may be easier to identify whether more concrete occurrences happened within a specific timeframe (e.g., Within the last 3 h, I interacted with a family member) compared to more subtle experiences which may be better measured over the course of a whole day (e.g., How melancholic did you feel today?). Interestingly, a study by Schuler et al (2019) found no significant differences between the retrospective reports of symptoms when compared to EMA-based reports of traumatic experiences. These findings may reflect the unique circumstances involved in recall of such experiences, which are inherently more emotionally extreme and may therefore be easier to recall, even retrospectively.…”
Section: Methodological Variation In Ema Researchmentioning
confidence: 92%
“…A weighted average that favors the moments immediately before the assessment? Or, as some research suggests, will their responses reflect the most intense perceived threat they experienced over the time window (Schuler et al, 2021)? Similar questions arise in our examination of mate-selection strategies.…”
Section: Formal Theory As a Set Of Tools For Theory Constructionmentioning
confidence: 99%
“…These drawbacks of EMA can be alleviated by asking participants about experiences since the last measurement occasion (c.f., Ben-Zeev et al, 2012;van Roekel et al, 2017;Fernandez, Fisher, & Chi, 2017;Rinner et al, 2019), or since some time index (c.f., Gloster et al, 2008;Priebe et al, 2013;Schuler et al, 2019). In this approach, participants are essentially required to recall and aggregate over some limited time interval.…”
Section: Ema: Moment-to-moment Affects Cognitions Events and Behaviourmentioning
confidence: 99%
“…In addition to affective experiences, a comparison between ERA and RA is typically used in the symptom domain, likely because ERA is better able to capture salient experiences in comparison to EMA. For symptoms, the results are much more diffuse, with some authors reporting higher RA scores for panic attacks (De Beurs, Lange & Dijck, 1992), alcohol use (Simpson et al, 2011) 12 , psychotic experiences (Ben-Zeev et al, 2012), PTSD symptoms (Campbell et al, 2017;Schuler et al, 2019), and social phobia (Rinner et al, 2019), while others have found relatively good congruence for OCD (Gloster et al, 2008) and PTSD (Naragon-Gainey et al, 2012) symptomatology. Mixed results have been reported for bulimia nervosa (Stein & Corte, 2003;Wonderlich et al, 2015) and borderline personality disorder (Solhan, Trull, Jahng & Wood, 2009;Mneimne et al, 2019) symptoms.…”
Section: A Difference Between Experiencing and Evaluating?mentioning
confidence: 99%